2018
DOI: 10.5194/acp-2018-394
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CCN activity of six pollenkitts and the influence of their surface activity

Abstract: <p><strong>Abstract.</strong> Pollenkitt is a viscous material that coats grains of pollen and plays important roles in pollen dispersion and plant reproduction. It may also be an important contributor to pollen water uptake and CCN activity. The chemical composition of pollenkitt varies between species, but has been found to comprise complex organic mixtures including oxygenated, lipid, and aliphatic functionalities. The mix of functionalities suggests that pollenkitt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…The role of surfactants in cloud droplet activation has been a recurring theme for modelling of organic aerosol cloud climate interactions 112. While it has been established that surface activity can impact single droplet activation through both lowering surface tension and from diminishing the solute effect by surface partitioning,36,12,13 the relative impact of these effects and their potential synergies under different conditions are currently not well constrained 9,10,14,15. This balance has been shown to significantly impact the predictions of global cloud droplet numbers and radiative forcing16 and is therefore important to understand in a fully prescriptive way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of surfactants in cloud droplet activation has been a recurring theme for modelling of organic aerosol cloud climate interactions 112. While it has been established that surface activity can impact single droplet activation through both lowering surface tension and from diminishing the solute effect by surface partitioning,36,12,13 the relative impact of these effects and their potential synergies under different conditions are currently not well constrained 9,10,14,15. This balance has been shown to significantly impact the predictions of global cloud droplet numbers and radiative forcing16 and is therefore important to understand in a fully prescriptive way.…”
Section: Introductionmentioning
confidence: 99%
“…Of atmospherically relevant surfactants, previous studies have focused on straight-chain fatty acids and their carboxylate salts4,5,11 and less surface active dicarboxylic acids 2124. Recently, more complex surface active mixtures, including atmospheric limonene-derived organosulphates,25 organic mixtures coating pollen grains called pollenkitt,12 and proxies for atmospheric humic-like substances (HULIS),13 have been interpreted in a Gibbs model framework to varying degrees of success.…”
Section: Introductionmentioning
confidence: 99%
“…The geographical dispersion of anemophilous plants largely relies on pollen dispersal, which in turn depends on the emission, transport and deposition of pollen grains; therefore, pollen plays a key role in the evolution of many ecosystems (Womack et al, 2010;Fröhlich-Nowoisky et al, 2016). In addition, PBAPs can serve as giant cloud condensation nuclei (CCN) and ice nucleating particles (INPs), significantly impacting the formation and properties of clouds and thus radiative balance and precipitation (Möhler et al, 2007;Ariya et al, 2009;Pratt et al, 2009;Pope, 2010;Pummer et al, 2012; Gute and Abbatt, 2018). It has also been proposed that PBAPs may have significant impacts on chemical composition of aerosol particles via heterogeneous and multiphase chemistry (Deguillaume et al, 2008;Estillore et al, 2016;Reinmuth-Selzle et al, 2017;Shiraiwa et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hygroscopicity is closely linked to the ability of aerosol particles to serve as CCN and INPs (Petters and Kreidenweis, 2007;Kreidenweis and Asa-Awuku, 2014;Tang et al, 2016). Several previous studies have measured the hygroscopicity and CCN activities of pollen (Diehl et al, 2001;Pope, 2010;Griffiths et al, 2012;Lin et al, 2015;Steiner et al, 2015;Prisle et al, 2018) and other PBAPs such as bacteria (Pasanen et al, 1991;Reponen et al, 1996;Franc and DeMott, 1998;Ko et al, 2000;Lee et al, 2002;Bauer et al, 2003). For example, water uptake of eleven pollen species was studied using an analytical balance (Diehl et al, 2001), and the mass of pollen was found to be increased by 3-16% at 73% RH and by ~100-300% at 95% RH, compared to that at 0% RH.…”
Section: Introductionmentioning
confidence: 99%
“…More recently Prisle et al . () found evidence in pollenkitt of six different plant species of its hygroscopicity in relation to its aqueous surface activity. According to Murphy () when pollen contacts the stigma its pollen coat reorganises and concentrates at the interface to form a bridge with hydrophilic channels of a probably proteic nature through which water transfers from stigma to pollen.…”
Section: Discussionmentioning
confidence: 99%